Colorimetric detection of class A soybean saponins by coupling DNAzyme with the gap ligase chain reaction. Issue 26 (19th June 2020) - Li, Wenshuai; Wu, Guorui; Wang, Min; Yue, Aiqin; Du, Weijun; Liu, Dingbin; Zhao, Jinzhong
Abstract : We propose a colorimetric assay based on the coupling of gap ligase chain reaction (Gap-LCR) with DNAzyme to detect the target GmSg-1 genes of class A soybean saponins with the naked eye, without the involvement of expensive instruments. Abstract : Class A saponins are responsible for the taste of soybean products, and the rapid identification of class A saponins from soybean food is essential for both food safety and cultivar screening. In this study, we propose a colorimetric assay based on the coupling of gap ligase chain reaction (Gap-LCR) with DNAzyme to detect the target GmSg-1 genes of class A soybean saponins with the naked eye, without the involvement of expensive instruments. The limits of detection (LODs) for the GmSg-1 a and GmSg-1 b genes were determined to be 0.1618 and 0.1625 μM, respectively, with a linear range of 0.2–1.2 μM. The DNAzyme-based Gap LCR assay was successfully employed to identify the target genes from different soybean cultivars, providing a simple means for monitoring the quality of soybean products.